2022
DOI: 10.1017/s0007114522003749
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability and cross-sectional and longitudinal validity of fifteen bioelectrical impedance analysis devices

Abstract: The purpose of this investigation was to expand upon the limited existing research examining the test-retest reliability, cross-sectional validity, and longitudinal validity of a sample of bioelectrical impedance analysis (BIA) devices as compared to a laboratory four-compartment (4C) model. Seventy-three healthy participants aged 19-50 were assessed by each of 15 BIA devices, with resulting body fat percentage (BFP) estimates compared to a 4C model utilizing air displacement plethysmography, dual-energy x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Body composition was not assessed via the DXA method due to a lack of availability [66] and funding. However, BIA has been showed to be a reliable [18] and valid [19,20] method if the specific testing guidelines [16,17] are followed. Moreover, in BIA measurements, it was reported that water content impacts the reactance and resistance of these measurements [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body composition was not assessed via the DXA method due to a lack of availability [66] and funding. However, BIA has been showed to be a reliable [18] and valid [19,20] method if the specific testing guidelines [16,17] are followed. Moreover, in BIA measurements, it was reported that water content impacts the reactance and resistance of these measurements [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the BIA measurement has been reported to be influenced by factors including electrodes, the operator, the subject, the environment [13], food, alcohol, physical exercise and the time of day [15]. However, following the necessary manufacturer and laboratory testing guidelines developed over time [16,17], the measurements have been shown to be reliable [18] and valid [19,20] compared to DXA. BIA testing reports several parameters like muscle mass, fat mass and body hydration status, among others [4], and has been widely used in judo research [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The same researcher performed the BIA test for all participants. It is important to note that BIA is not the gold standard for body composition evaluation, and although it is not a primary outcome in this study, the BIA results depend on BIA-based predictive equations with oscillating values depending on the formula applied and device [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many of these studies merely mention the type of software employed, making it impossible to discern which formulas were used to convert raw bioelectrical parameters into components of body mass. Furthermore, such data may no longer be representative over time because companies producing such software can alter the equations without notifying users [ 29 ]. While this approach is undoubtedly quicker than a systematic and accurate selection of the most appropriate equation among those available in the literature, does not guarantee a high-standard validity.…”
Section: Introductionmentioning
confidence: 99%